The effects of water stress and plant density on vegetative and reproductive characteristics of safflower in the semi-arid region - Hasan KOUCHAKKHANI; Mohsen JANMOHAMMADI; Naser SABAGHNIA (Studia Universitatis Babeș-Bolyai. Biologia, 2024)
The limited availability of water for irrigation in semi-arid areas necessitates the use of deficit irrigation techniques. Deficit irrigation is an irrigation practice whereby water supply is reduced below maximum levels and a mild water-deficit stress affects the crop yield. Current field experiment was aimed to investigate different densities of safflower (Carthamus tinctorius L.) (33, 40, 50, 66 plants m2 abbreviated as P33, P40, P50, and P66, respectively) under different soil moisture content (irrigation up to 100%, 70%, and 50% field capacity showed as FC100, FC70, and FC50, respectively) on the growth characteristics of safflower in a semi-arid region in the northwest of Iran. The number of days to maturity decreased significantly under deficit irrigation (FC70 and FC50). The longest growth period was recorded for plants growing under P66-FC100 conditions which was 7% higher than P50-FC100. The decrease in plant density caused an increase in chlorophyll content and this trend was more evident under Fc100. Increasing the density under FC100 conditions increased the plant height. However, this trend was not observed under deficit irrigation conditions. Decreasing the plant density per unit area induced lateral growth, and increased the number of capitula per plant, the weight of capitulum, the number of achenes per capitulum and the 1000-achenes weight. This trend was more prominent under FC100 conditions. Mild deficit-irrigation (irrigation up to FC70) resulted approximately 20% reduction in achene yield. Thus, water management is very important to certify a conservational water supply in semi-arid regions. Irrigation up to FC70 under the studied area is a reasonable and good management method to save irrigation water.